Urgensi Penetapan Kebutuhan ASN Untuk Menghindari Permasalahan Yang Timbul - Indriyani Anita; Joko Tri Hasbi; Jhosephin Virani Triani Rahail; Adji Suradji Muhammad (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Improving the performance of government agencies requires first accurately determining the needs for Civil Servants (ASN). This study analyzes many problems that occur in the application of the Ministry of State Apparatus Empowerment and Bureaucratic Reform's (PANRB) policies for determining ASN needs. Even with Law Number 5 of 2014 requiring every agency to plan personnel needs based on analysis, problems such imprecise needs calculations, inadequate inter-agency collaboration, and inadequate use of IT still exist. This article examines the guidelines and practices for assessing ASN requirements and offers suggestions for enhancing the efficacy and efficiency of these guidelines. It is envisaged that the proposed changes will make determining ASN needs more optimal in supporting government agency performance.